2023
DOI: 10.3390/jpm13040609
|View full text |Cite
|
Sign up to set email alerts
|

Breast Density Evaluation According to BI-RADS 5th Edition on Digital Breast Tomosynthesis: AI Automated Assessment Versus Human Visual Assessment

Abstract: Background: The assessment of breast density is one of the main goals of radiologists because the masking effect of dense fibroglandular tissue may affect the mammographic identification of lesions. The BI-RADS 5th Edition has revised the mammographic breast density categories, focusing on a qualitative evaluation rather than a quantitative one. Our purpose is to compare the concordance of the automatic classification of breast density with the visual assessment according to the latest available classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A p < 0.05 was considered statistically significant, with a 95% confidence interval. According to Landis J.R. and Koch G.G., the kappa values were interpreted as follows: 0.0-0.20, slight agreement; 0.21-0.40, fair agreement; 0.41-0.60, moderate agreement; 0.61-0.80, substantial agreement; 0.81-1.00, almost perfect agreement [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A p < 0.05 was considered statistically significant, with a 95% confidence interval. According to Landis J.R. and Koch G.G., the kappa values were interpreted as follows: 0.0-0.20, slight agreement; 0.21-0.40, fair agreement; 0.41-0.60, moderate agreement; 0.61-0.80, substantial agreement; 0.81-1.00, almost perfect agreement [4].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of laboratory tests (PT, PTT, INR, platelet count) (3) DBT images evaluation (to choose the correct gauge and aperture of the needle) VABB examination (4) Full explanations of the procedure (written informed consent; is there psychological stress? )…”
Section: Guidelines For Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…3 Previous studies have demonstrated the effectiveness of AI models and radiomics features in reducing inter-reader variability. [4][5][6] By automating the interpretation process and providing consistent assessments, AI has the potential to significantly improve the accuracy and efficiency of breast density identification.…”
mentioning
confidence: 99%